Thieme Chemistry Journals Awardees – Where Are They Now? Ribosylation of an Acid-Labile Glycosyl Acceptor as a Potential Key Step for the Synthesis of Nucleoside Antibiotics - Wiegmann, Daniel; Spork, Anatol P.; Niro, Giuliana; Ducho, Christian (Synlett, 2018)
Naturally occurring nucleoside antibiotics (e.g., muraymycins and caprazamycins) represent attractive lead structures for the development of urgently needed novel antibacterial agents. One major challenge in the total synthesis of muraymycins, caprazamycins, and their analogues is the efficient construction of the densely functionalized aminoribosylated uridine-derived core unit. In order to avoid tedious protecting-group manipulations, we have aimed to conduct the aminoribosylation step with an acid-labile glycosyl acceptor. Therefore, different glycosylation approaches have been studied, with pentenyl glycosides giving the best results.
Keywords: natural products; antibiotics; nucleosides; glycosylation; ribosylation; pentenyl glycosides